A photosensitive-type CPL response controlled by intermolecular dynamic FRET and chiral transfer in ternary chiral emissive nematic liquid crystals. Issue 37 (19th August 2021) - Yao, Kun; Li, Yang; Shen, Yihao; Quan, Yiwu; Cheng, Yixiang
Abstract : The chiral emitting ternary liquid crystals (T-N*-LCs) exhibited a photosensitive-type red CPL response controlled by an intermolecular dynamic Förster resonance energy transfer (FRET) mechanism. Abstract : The development of excellent circularly polarized luminescence (CPL) materials with both a high luminescence dissymmetry factor ( g lum ) and high quantum yield ( Φ lum ) is crucial for realizing 3D displays. Herein, we prepared chiral-emitting ternary liquid crystals (T-N*-LCs) containing the chiral binaphthyl dopant R / S -BF (a chiral inducer and energy donor) and the achiral dye Nile Red (a CPL emitter and energy acceptor) using the commercial nematic liquid crystals E7 (N-LCs) as a host. These ternary N*-LCs exhibited a photosensitive-type red CPL response controlled by an intermolecular dynamic Förster resonance energy transfer (FRET) mechanism. Under irradiation with 365 nm ultraviolet light (hand-held 1.0 mW cm −2 UV light), the binary-emitting liquid crystals containing R / S -BF in E7 showed a transition from a strong green CPL signal ( λ em = 480 nm, g lum = +0.28/−0.25) to weak blue CPL ( λ em = 438 nm, g lum = +0.03/−0.028) due to the Z -to- E isomerization of R / S -BF. Interestingly, T-N*-LCs loaded with the energy receptor Nile Red exhibited interconversion between a "strong" and "weak" red CPL response before and after irradiation with 365 nm UV light, which can be attributed to an intermolecular dynamic FRET process based on different overlap between the absorption of the acceptor (NR) and the distinct emissions of the Z - and E -isomers of the donor R / S -BF. Strong red CPL emission ( g lum = +0.63/−0.65, λ em = 625 nm) was observed due to the high helical twisting power of Z-R / S -BF and efficient FRET from Z-R / S -BF to NR. This work paves the way for the construction of chiral optical information storage with photochromic change functionality.